Between a guest and an okupa: Migration and the making of insurgent citizenship in Buenos Aires' informal settlements - Tanja Bastia (2018)
In this paper, we explore initiatives for the construction of substantive citizenship by transnational migrants in Buenos Aires. In looking at migrants’ political participation across the city, we found that the spatiality of citizenship practices is important. At the city level, there are migrant organisations representing specific nationalities. However, in informal settlements, where many migrants reside, we found that migrants engage in political practices across nationality and ethnic lines by coming together with their neighbours in grassroots organisations. These different forms of organising embody critically different views of migrants in their relationship with rights. While the former promote practices linked to ethnic belonging and see migrants as ‘guests’ in a foreign country, unable to make claims to the local or national governments, the latter see them as rights-bearing individuals with power to claim their right to the city. We argue that activism at the scale of the neighbourhood proves to hold more potential for the building of substantive citizenship than actions by organisations active at the city level. This is because migrant organisations active at the city level organise on the basis of nationality, while those at the neighbourhood level bring migrants and non-migrants together on the basis of their class-based interests.